Attitudes of South African teacher educators in relation to mainstreaming pupils with special needs - Choles, Gwynneth, May (My University, 1997)
The policy of mainstreaming and the provision for learners with Special Educational Needs (SEN) in the regular classroom is being promoted in many countries. The rationale for this study lies in the pivotal role of teacher educators In facilitating the success of mainstreaming. ( Abbreviation abstract )
A Dissertation Presented to The Division of Specialized Education The University of the Witwatersrand In Partial Fulfillment of the Requirements for the Degree of Master of Education (Educational Psychology)
Keywords: Mainstreaming in education -- South Africa.; Special education -- South Africa.; Teacher educators -- South Africa -- attitudes